2003
DOI: 10.1099/jmm.0.05132-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression stability of six housekeeping genes: a proposal for resistance gene quantification studies of Pseudomonas aeruginosa by real-time quantitative RT-PCR

Abstract: Constantly expressed genes are used as internal controls in relative quantification studies. Suitable internal controls for such studies have not yet been defined for Pseudomonas aeruginosa. In this study, the genes ampC, fabD, proC, pbp-2, rpoD and rpoS of P. aeruginosa were compared in terms of expression stability by real-time quantitative RT-PCR. A total of 23 strains with diverse resistance phenotypes were studied. Stability of expression among the housekeeping genes was assessed on the basis of correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
211
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(221 citation statements)
references
References 24 publications
8
211
0
2
Order By: Relevance
“…[10][11][12][13] In this study, 50 P. aeruginosa isolates from the patients with LRTIs in ICU were investigated for 13 genes, mostly for efflux proteins leading to antimicrobial resistance. To our knowledge, although there are studies investigating the resistance genes from Turkey, 14,15 there aren't any studies investigating a large number of resistance genes in P. aeruginosa strains isolated from nosocomial LRTIs. The results of the study have shown antimicrobial resistance rates of the isolates were found high, and 86% of them were determined to carry at least one resistance gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12][13] In this study, 50 P. aeruginosa isolates from the patients with LRTIs in ICU were investigated for 13 genes, mostly for efflux proteins leading to antimicrobial resistance. To our knowledge, although there are studies investigating the resistance genes from Turkey, 14,15 there aren't any studies investigating a large number of resistance genes in P. aeruginosa strains isolated from nosocomial LRTIs. The results of the study have shown antimicrobial resistance rates of the isolates were found high, and 86% of them were determined to carry at least one resistance gene.…”
Section: Resultsmentioning
confidence: 99%
“…P. aeruginosa strains (fifty) were isolated from tracheal aspirate (27), bronchoalveolar lavage (14) and sputum (9). Isolates were identified as P. aeruginosa based on colony morphology, odor, Gram staining, production of blue-green pigment on Mueller Hinton agar, reactions (k/k) on triple sugar iron agar slants, positive oxidase reaction.…”
Section: Bacterial Strainsmentioning
confidence: 99%
“…Primers used in this study (RQ-785, RQ-962, RQ-223, rpoD, forward and reverse) were specifically designed to give PCR products around 150 base pair (Supplemental Table 1). Expression levels of paazor1, paazor2 and paazor3 were detected by quantitative RT-PCR analysis with a LightCycler (Roche) in comparison with expression of a P. aeruginosa σ factor rpoD (Savli et al, 2003). Each amplification mixture (10 μL QuantiTect 2 × SYBR Green PCR master mix (Qiagen), 0.5 μg cDNA, 0.5 μM suitable primers and sterile water in a total 20 μL) was subjected to the following thermo-cycling program: one cycle of 95°C for 15 min to activate the HotStart Taq DNA polymerase; 40 cycles of denaturation (94°C for 15 s), annealing (60°C for 20 s), extension (72°C for 15 s) and data acquisition (65°C for 5 s).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…Bacteria were collected from the edge of swarming bacterial colonies, and the RNA was extracted using a Qiagen RNeasy Midi kit (Qiagen, German- For real time PCR quantification using the cDNAs of P. aeruginosa PAO1 and MPA45, primer sets specific for genes fliC, fliD, fliM, flgM, PA4915, and cheY were designed using the Primer Express software under the factory default settings. Two housekeeping genes, rpoD and proC, were used as an internal control of gene expression, and the mean of the proC and rpoD expression levels in the sample was used as the normalization factor (23). All primers were tested for the absence of nonspecific bands or primer dimer formation prior to real time PCR analysis.…”
Section: Methodsmentioning
confidence: 99%